Association of biallelic RFC1 expansion with early-onset Parkinson's disease - Ylikotila Pauli; Sipilä Jussi; Alapirtti Tiina; Ahmasalo Riitta; Koshimizu Eriko; Miyatake Satoko; Hurme-Niiranen Anri; Siitonen Ari; Doi Hiroshi; Tanaka Fumiaki; Matsumoto Naomichi; Majamaa Kari; et al. (Wiley, 2025)
Background and purpose: The biallelic repeat expansion (AAGGG)exp in the replication factor C subunit 1 gene (RFC1) is a frequent cause of cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) as well as late-onset ataxia. The clinical spectrum of RFC1 disease has expanded since the first identification of biallelic (AAGGG)exp and includes now various nonclassical phenotypes. Biallelic (AAGGG)exp in RFC1 in patients with clinically confirmed Parkinson's disease (PD) has recently been found.
Methods: A nationwide cohort of 273 Finnish patients with early-onset PD was examined for the biallelic intronic expansion in RFC1. The expansion (AAGGG)exp was first screened using extra long polymerase chain reactions (Extra Large-PCRs) and flanking multiplex PCR. The presence of biallelic (AAGGG)exp was then confirmed by repeat-primed PCR and, finally, the repeat length was determined by long-read sequencing.
Results: Three patients were found with the biallelic (AAGGG)exp in RFC1 giving a frequency of 1.10% (0.23%-3.18%; 95% confidence interval). The three patients fulfilled the diagnostic criteria of PD, none of them had ataxia or neuropathy, and only one patient had a mild vestibular dysfunction. The age at onset of PD symptoms was 40-48 years and their disease course had been unremarkable apart from the early onset.
Conclusions: Our results suggest that (AAGGG)exp in RFC1 is a rare cause of early-onset PD. Other populations should be examined in order to determine whether our findings are specific to the Finnish population.